The effect of using Active Learning Strategy in acquiring rhetoric & application material and Keeping it for secondary stage Pupil . (Journal of the College of Basic Education, 2022)
The present paper is aiming to identify the effect of numbered heads strategy in acquiring rhetoric and application material and keeping it for secondary school female pupils where the research sample was totaled to 60 pupils, in reality of 30 pupils serving as experimental group to study rhetoric and application according to numbered heads strategy, to be represented by class (B), and 30 pupils serving as controlling group who studied the same material in the traditional / usual way and they were represented by class (A).The researcher prepared a gaining test consisted of 30 items of choosing from multi and after extracting the appearant validity, the test was applied on flying sample to identify hardness, the distinguishing power, the activity of the alternatives for after then identify the stability, after that the test in its find form was applied on the research sample, then the test was reapplied to measure the range of pupil keeping for the rhetorical information and that was for the sample under search, the results showed and after treating them statistically by using T-test the following:The existing of difference of statistical reference at level of 0.05 and for the benefit of the group under the experiment the gaining after and keeping tests.